Metode, Sumber dan Corak Tafsir Pada Penulisan Kitab Tafsir Isyaratul I’jaz Karya Said Nursi - Ghinaurraihal Ghinaurraihal; Eni Zulaiha; Badruzzaman M. Yunus (UIN Sunan Gunung Djati Bandung, 2021)
One of the works of interpretation belonging to Badiuzzaman Said Nursi and the first commentary that he wrote was the interpretation of Signs of I'jaz. The book of interpretation has many features and uniqueness when compared to his other works. Despite being a prima donna among literary experts, this interpretation is less attractive to the general public. The discussion of the interpretation of the Qur'anic verses using language that is quite high turns out to make it difficult for some people to understand. This study aims to examine the sources, methods, and styles used by Said Nursi in writing the interpretation of Isaatul I'jaz. This research is qualitative research by applying the library research method as a way of processing data. From this research, conclusions can be drawn regarding the tahlili method as a method of interpretation. Interpretations that tend to lead towards faith, divinity, and worship are included in the i'tiqadi-style interpretation. Said Nursi uses the Qur'an as the primary source of interpretation, then there are also several previous commentary books as a secondary source of writing his commentary.